Healthy Workplace through Increasing Healthy Lifestyle and Personal Health Skills in Sidoarjo, East Java, Indonesia - Ratna Dwicahyaningtyas; Riris Diana Rachmayanti; Soedarwanto Soedarwanto (The Indonesian Journal of Occupational Safety and Health, 2021)
Introduction: Creating a healthy workplace is a form of workplace health promotion that enables workers to have control on their health, supports workers to work on their best and increases productivity. The major components of healthy workplace are healthy lifestyle and personal health skills. In an internationally qualified catering service company, workers have to work on a busy schedule. The purpose of this research is to describe the health promotion activities, specifically about healthy lifestyle and personal health skills at a catering service company. Methods: This research was a qualitative study, with a population of 488 workers, and a sample of 5 informants from Human Capital (HC) and Quality, Health, Safety, and Environment (QHSE) Department. Primary data were collected through interviews with employees as informants using an interview guide, and the observation was performed throughout the workplace based on a checklist instrument. Meanwhile, the secondary data were obtained from company’s documents. The data obtained were analyzed descriptively to portray the situation. Results: This company provides various programs and facilities to support employees to adopt healthy lifestyles and improve their health-related personal skills through mandatory and functional training programs that are integrated in the workplace, provision of healthy nutritious foods at the office canteen, a smoking area, physical activities, counseling, and maternity leave for female employees. Conclusion: Programs and facilities provided by the company are sufficient to help workers to carry out healthy lifestyles and work up on their skills to be conducive for their health, and improvement on the smoking area is needed to meet the existing regulation.Keywords: health promotion, lifestyle, personal health skills, workplace